Spirituality management in the workplace : new strategies and approaches - Özsungur, Fahri; Bekar, Fevziye (Emerald Publishing Limited, 2023)
In recent years, after realizing that personal beliefs and spiritual development are as important as mental strength, studies in the field of spirituality in the workplace have grown exponentially. The experts here provide conceptual frameworks and guidance by examining the subject in the light of current developments at multiple levels of analysis: individual, organizational, cultural, and in leadership. Furthermore, this book focuses on rapidly evolving business models: remote working, the cyber-workplace, social media, digitalization, etc - all accelerated by the COVID-19 epidemic. The concept of spirituality in the workplace can be harmful as well as beneficial. Employees who are spiritually attached to the workplace may ignore issues known as 'organizational deviation' (such as theft and corruption) by keeping the interests of the institution in the foreground. These 'dark' and 'invisible' aspects of spirituality in the workplace are also examined, with a special focus on identifying aspects of spirituality which can harm businesses. Spirituality in the workplace considers employees as a whole, in spirit, body, and mind.
Includes index.
Keywords: Corporate culture.; Spirituality.; Business & Economics, Workplace Culture.; Office & workplace.; elektronické knihy; electronic books